Enhanced intestinal epithelial co-culture model with orbital mechanical stimulation: a proof-of-concept application in food nanotoxicology - Santoni, Mattia; Piccinini, Giovanni; Liguori, Giovanni; Randi, Maria Roberta; Baroncini, Massimo; Milani, Liliana; Danesi, Francesca (Frontiers in Molecular Biosciences, 2025)
IntroductionCurrent in vitro intestinal models lack the mechanical forces present in the physiological environment, limiting their reliability for nanotoxicology studies. Here, we developed an enhanced Caco-2/HT29-MTX-E12 co-culture model incorporating orbital mechanical stimulation to better replicate intestinal conditions and investigate nanoparticle interactions.MethodsWe established co-cultures under static and dynamic conditions, evaluating their development through multiple approaches including barrier integrity measurements, gene expression analysis, and confocal microscopy. We introduced novel quantitative analysis of dome formation as a differentiation marker and demonstrated the model application by investigating cellular responses to titanium dioxide (TiO₂) nanoparticles in a digested food matrix.ResultsDynamic conditions accelerated epithelial differentiation, achieving functional barrier properties by day 14 rather than day 21, with enhanced mucin production and more organized three-dimensional structure. Mechanical stimulation selectively promoted goblet cell differentiation without affecting general epithelial markers. The optimized model successfully detected concentration-dependent oxidative stress responses to TiO₂ exposure, revealing cellular dysfunction preceding membrane damage.DiscussionThis improved co-culture system provides a better physiological platform for nanotoxicology studies. By incorporating mechanical forces, each cell type exhibits more representative behavior, creating a more realistic experimental setup. The model bridges the gap between simple monocultures and complex 3D systems, offering a practical approach for investigating nanoparticle-epithelium interactions in a food-relevant context.